A Model of Implementing Restorative Justice Perspective of Trong Yowari Traditional Jurisdiction, Jayapura Regency - Maryani, Desy; Elvis Rahael, Arie; Rahawarin, Ahmad; Ariyanto; Muslim; Farida Tuharea; Rumalean, Zonita Zirhani; Wahyudi BR (NUSANTARA: Journal Of Law Studies, 2023)
This study aims to know and understand the policy of implementing restorative Justice in the judiciary. As well as to know and understand the model of implementing restorative Justice from the perspective of the customary Justice of the Trong Yowari tribe, Jayapura Regency. The method used in this study is empirical juridical research that takes place in the Trong Yowari tribe, Jayapura Regency, with secondary data types with primary, secondary, and tertiary legal data sources, the population of the entire Trong Yowari tribe and samples in Yongsu Desoyo village, data collection techniques through literature study or documents with data analysis techniques using descriptive qualitative data analysis. The results of the study indicate that the policy of implementing restorative Justice in the prosecutor's office is the authority of the public prosecutor to stop prosecution if a case has been settled outside the court provided that: (a) for certain matters of crime, the maximum fine is paid voluntarily or (b) has recovery occurs back to its original state by using a Restorative Justice approach